Students' Expectations of Accounting's Role in Ensuring Business Sustainability - Sharon, St Salmah; Jafar, Adindah Novihartina; Suade, Yuyun Karistin Meilisa (Technium Sustainability, 2025)
This research aims to explore student expectations regarding the role of accounting in understanding and applying the concept of business sustainability through in-depth interviews. In a business context that is increasingly focused on sustainability, accounting has become crucial in measuring, reporting and guiding sustainable business decisions. Through interviews with students, their expectations regarding the role of accounting for business sustainability are reflected in various aspects. First, accounting measures a company's sustainability performance by monitoring the environmental, social and economic impacts of business activities. Second, accounting provides a framework for preparing transparent and informative sustainability reports, helping to meet stakeholder needs. Third, accounting helps companies identify, evaluate and manage risks and opportunities related to business sustainability. Fourth, accounting facilitates the assessment of a company's long-term value by considering the social, environmental, and economic impacts of business operations. Fifth, information produced by accounting guides company management in making strategic decisions that support sustainable business growth and build a strong reputation in the eyes of stakeholders. Through a better understanding of the role of accounting in the context of business sustainability, students expressed their belief that accounting is a tool for shaping a more responsible and socially and environmentally sustainable business future.